Impact assessment for just transition of protein production systems - Harpinder Sandhu; Amie Sexton; Priyambada Joshi; Lee Recht; Ayon Chakraborty; Sukhbir Sandhu (PLoS ONE, 2025)
Understanding the impacts of protein production systems is necessary to plan the just transition of food systems. We analysed 285 studies to assess the impacts of 13 protein systems across 25 indicators under five key categories—natural capital, human capital, social capital, produced capital and governance. Nine protein systems (regenerative, organic, rangelands, free-range poultry, sustainable energy cultivated meat, conventional energy cultivated meat, mixed grains and livestock, pastoralists and plant-based) have overall positive impacts across all five categories. In comparison, four protein systems have negative impacts (small-scale beef, caged poultry, industrial pork, and confined feeding operations). We then used this in-depth assessment to develop five ‘what if’ future scenarios to track and assess the transition of protein production systems to 2050. Rapid reduction of industrial production may contribute to a just and inclusive transition of protein production systems. This assessment can help reduce risks associated with negative impacts and assist in governing and managing protein production systems towards long-term sustainability.